The Role of Perception of Usefulness and Interest in Using E-Filing for Individual Income Tax - Indah Masri; Amelia Oktrivina; Ayu Woro Angelina (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
This study aims to see the role of external factors such as speed, subjective norms, and understanding of taxation in increasing the use of E-Filing. In addition, this study also aims to see the role of internal factors related to attitudes and behaviors such as perceptions and interests in using E-Filing in increasing the use of E-Filing. Speed has no significant negative influence on the use of E-Filing. Subjective norms have a positive and significant influence on the use of E-Filing. Understanding of taxation has no significant positive influence on the use of E-Filing. The perception of the usefulness of E-Filing has a positive and insignificant influence on the use of E-Filing. Interest in using E-Filing has a positive and significant influence on the use of E-Filing.